Montagem de posicionador de varredura bidimensional automatizada acoplado a espectrometria de fluorescência de raios X - Leonardo Santiago Melgaco Silva (2011)
This present work describes the design and assembling of a prototypeautomated positioner two-dimensional scanning coupled to X-ray fluorescence spectrometry. The work aims to achieve a portable and easy to use, device of broad utility in the analysis of samples by X-ray fluorescence area of expertise and research. The two-dimensional scanning of the positioner is by means of two stepper motors controlled by a microcontroller PIC 16F877A, encoder and optical sensors. The user interacts with the XY table through an interface program for the Windows operating system, which communicates with the microcontroller through the serial port. The system of Fluorescence Spectroscopy incorporated into the positioner consists of a system commercially available system from the company AMPTEK, where the primary source of excitation of the sample was a source of 241Am of 59.5 KeV emissions. Resolution and accuracy of tests were performed in the XY scanning process and reproducibility of the same kit with the fluorescence spectrometry X-ray. Qualitative tests by X-ray fluorescence spectrometry in samples wereperformed to demonstrate the applicability and versatility of the project. Itfollows that the prototype illustrates a possible adequately to portable device for X-ray spectrometry of two-dimensional.